THE APLICATION OF LEARNING MODEL PBI TO IMPROVED THE LEARN OUTCOMES OF BASKETBALL DRIBBLE OF STUDENTS ON 7TH GRADE (STUDY AT MTS BADRUSSALAM SURABAYA JUNIOR HIGH SCHOOL) - PRASETYO UTOMO, ERWAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstrak Model pembelajaran problem based instruction (PBI) adalah model pembelajaran yang pada praktek pembelajaran, guru memberikan sebuah masalah kepada siswa dan harus dipecahkan baik secara kelompok maupun individu. Yang kemudian ditampilkan dan dievaluasi bersama dalam kelas. Sehingga model pembelajaran ini akan membentuk suasana belajar yang membuat siswa lebih aktif dibanding dengan guru dan mudah untuk mencapai tujuan pembelajaran yang telah ditetapkan. Hasil belajar adalah indikator pencapaian peserta didik terhadap pembelajaran selama proses belajar mengajar berlangsung. Dan bolabasket adalah permainan beregu yang dimainkan oleh dua tim yang beranggotakan masing-masing lima orang. Yang memiliki beberapa teknik dasar. yaitu drible, passing dan skoring. Hasil belajar drible bola basket adalah pencapaian peserta didik tentang proses pembelajaran drible bola basket berdasarkan pada indikator pencapaian. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar drible bola basket siswa dengan menggunakan model pembelajaran Problem Based Instruction (PBI) pada siswa kelas VII MTs Badrussalam Surabaya. Berdasarkan hasil dari penelitian yang menggunakan tes drible 60 detik menunjukkan ada peningkatan hasil belajar siswa pada setiap siklusnya. Dengan mengetahui hasil dari penelitian ini, maka dapat memberikan data dan informasi bagi guru Penjasorkes bahwa model pembelajaran Problem Based Instruction (PBI) dapat meningkatkan hasil belajar siswa. Khususnya pada pembelajaran drible bola basket. Kata Kunci: Hasil belajar dribble Bola basket siswa, Model pembelajaran Problem Based Instruction (PBI) Abstract The learning model Problem Based Instruction (PBI) is a learning model on the practice of learning, theacher give a students problems and must be solve either by group or individual. Which is then shown and evaluated together in the class. So this learning model is will compose an atmosphere of learning that make students more active compared with the teacher and is easy to reach the objectives that have been set. The learn outcomes are indicator of achievement of learners during a learning process.  And basketball is game group which played by two team with five players at each team and have some basic techniques. That is dribble, pass, and score. So the learn outcome of basketball dribble is achievement of the learners about of basketball driblle learning based on indicators of achievement. The purpose of this research is for know the learn outcomes of basketball dribble improvement with aplication of learning model Problem Based Instruction (PBI) on 7th grade students at MTs Badrussalam Surabaya. Based on the result of research who used 60s static dribble test show their is improvement the learn outcomes of students at each cycle. By knowing this, than the result of research can provide data and information for theachers penjasorkes that the learning model Problem Based Instruction (PBI) could improve students learn outcomes. In particular the study of basketball dribble. Keywords: students learn becomes of basketball dribble, Learning model Problem Based Instruction (PBI)